2017
DOI: 10.1145/3110255
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic conditioning of arrays in probabilistic programs

Abstract: Probabilistic programming systems make machine learning more modular by automating inference. Recent work by Shan and Ramsey makes inference more modular by automating conditioning. Their technique uses a symbolic program transformation that treats conditioning generally via the measure-theoretic notion of disintegration. This technique, however, is limited to conditioning a single scalar variable. As a step towards modular inference for realistic machine learning applications, we have extended the disintegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Our base-measure language (Figure 22) includes discrete-continuous mixtures over R, dependent products, and disjoint sums; we also allow specifying the base measure as another probabilistic program (Section 7). Thus, our work subsumes all but Narayanan and Shan's [2017] and Roberts et al's [2019] handling of arrays, and is the first to allow different base measures over the same type.…”
Section: Gibbs Samplingmentioning
confidence: 97%
See 3 more Smart Citations
“…Our base-measure language (Figure 22) includes discrete-continuous mixtures over R, dependent products, and disjoint sums; we also allow specifying the base measure as another probabilistic program (Section 7). Thus, our work subsumes all but Narayanan and Shan's [2017] and Roberts et al's [2019] handling of arrays, and is the first to allow different base measures over the same type.…”
Section: Gibbs Samplingmentioning
confidence: 97%
“…Shan and Ramsey [2017] showed that disintegration is also a useful probabilistic-program transformation, but only automated it for base measures that are independent products of Lebesgue and counting measures. Narayanan and Shan [2017] generalized those independent products to handle arrays without unrolling. Any disintegration program transformation can also be used to find densities, because the totaling map .…”
Section: Disintegrationmentioning
confidence: 99%
See 2 more Smart Citations
“…When an observed quantity is not drawn directly from a primitive distribution, but rather a result computed by the model (such as the center of mass of random particles [1]), it is more involved to specify and implement the disintegration program transformation turning (16) into (18) [13,17]. In particular, we recently extended automatic disintegration to applications where the distribution of the observation has no density with respect to the Lebesgue base measure.…”
Section: Disintegrating a Joint Measurementioning
confidence: 99%